Pengaruh Daya Tarik Iklan, Harga dan Kualitas Produk terhadap Keputusan Pembelian Produk Emina Cosmetics di Kota Surabaya - Fortona, Danarusvita Hikma; Aisah, Siti (Peneliti.net, 2023)
This study aims to analyze the factors that influence consumer purchasing decisions for Emina Cosmetics products in Surabaya. In this quantitative study, 102 respondents were selected using non-probability and quota sampling methods. Data was collected through a questionnaire that explored consumer perceptions of advertising appeal, price, product quality, and purchasing decisions. The results showed that advertising attractiveness and purchasing decisions have a significant partial effect, while price does not have a significant partial effect. However, simultaneously, advertising attractiveness, price, and product quality have an effect on purchasing decisions. It can be concluded that consumers tend to choose products with good quality supported by attractive advertisements. These results provide important insights for Emina Cosmetics in designing effective marketing strategies to maintain and increase its market share in this competitive cosmetics industry.